PERUBAHAN PARADIGMA PEMASARAN: STUDI LITERATUR PERALIHAN DARI EKSKLUSIVITAS PRODUK KE NILAI SOSIAL : Shifting from Exclusivity to Social Value: A Literature Review of Marketing Philosophy Evolution - Septia, Nindirah; Ni Luh Putu Adinda Tasya Saraswati; Mahesa Krishna; Nadia Dara Ayundha; Nani Asrini (ABISATYA DINAMIKA ISWARA, 2025)
ABSTRACT Background: The shift in marketing paradigm reflects a transition from a focus on product exclusivity to an emphasis on social value. Increasing social and environmental awareness compels companies to integrate social values into their marketing strategies. Objective: This paper aims to explore this shift and analyze its impact on consumer behavior and more sustainable marketing strategies. Method: This research was conducted through a systematic literature review. A total of 20 relevant academic sources were selected based on inclusion and exclusion criteria, including articles discussing social marketing, the impact of social values, and consumer behavior. Results: The analysis results indicate that companies adopting social values in their marketing not only enhance brand image but also foster customer loyalty. However, challenges such as the risk of